Nerd Ecology Defending the Earth with Unpopular Culture - Lioi, Anthony (Environmental Cultures, 2016)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. Drawing on a wide range of examples from literature, comics, film, television and digital media, Nerd Ecology is the first substantial ecocritical study of nerd culture's engagement with environmental issues. Exploring such works as Star Trek, Tolkien's Lord of the Rings, The Matrix, Joss Whedon's Buffy the Vampire Slayer and Firefly, the fiction of Thomas Pynchon, The Hunger Games, and superhero comics such as Green Lantern and X-Men, Anthony Lioi maps out the development of nerd culture and its intersections with the most fundamental ecocritical themes. In this way Lioi finds in the narratives of unpopular culture - narratives in which marginalised individuals and communities unite to save the planet - the building blocks of a new environmental politics in tune with the concerns of contemporary ecocritical theory and practice.